1981
DOI: 10.1097/00005072-198111000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Comparison of the Vulnerability of Peripheral Motor and Sensory Neurons in Amyotrophic Lateral Sclerosis

Abstract: The diameter histograms of cell bodies (cytons) in motor neuron columns at the L5 segment of the spinal cord of adult man reproducibly yield three peaks of increasing height: small (Cs), intermediate (Ci), and large (Cl). Histograms of L5 myelinated axons obtained from the ventral root have two peaks of increasing height: intermediate (Ai) and large (Al). In histograms prepared from seven cases of amyotrophic lateral sclerosis (ALS), the Cl and Al peaks were decreased selectively and severely. This provides ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(110 citation statements)
references
References 0 publications
5
105
0
Order By: Relevance
“…Similar alterations are seen in ALS patients, where there appears to be a selective degeneration of ␣ motor neurons with large axonal diameters, whereas motor neurons with small axonal calibers (␥ motor neurons) are spared (24,25). Axonal atrophy and loss of large fibers is also reported to be associated with aging (26,27).…”
Section: Discussionmentioning
confidence: 63%
“…Similar alterations are seen in ALS patients, where there appears to be a selective degeneration of ␣ motor neurons with large axonal diameters, whereas motor neurons with small axonal calibers (␥ motor neurons) are spared (24,25). Axonal atrophy and loss of large fibers is also reported to be associated with aging (26,27).…”
Section: Discussionmentioning
confidence: 63%
“…In this study we use a combination of three molecular markers of γ-MNs-the Hb9::GFP transgene, NeuN, and the GDNF receptor reporter Gfrα1-TLZ-to demonstrate complete and selective sparing of γ-MNs even at late stages of disease in three unrelated transgenic models of ALS respectively expressing mutant SOD1 G93A , TDP-43 A315T , or FUS P525L . Together, these independent markers enable us to identify γ-MN cell bodies in the ventral horn of the spinal cord of these mutants and to address the possibility that the loss of individual markers and changes in MN morphology (29) in the mutant mice may have led to the misidentification of shrunken α-MNs as γ-Μs, a criticism that limited several previous studies suggesting γ-MN sparing in ALS patients and in the SOD1 mouse model (22)(23)(24)(25)(26). Moreover, we demonstrate that the majority of NMJs on muscle spindles of the TA muscle remain innervated at end stage, consistent with the complete sparing of γ fusimotor axons that contact ∼90% of intrafusal NMJs (17).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that in ALS patients and mouse models of disease the average soma size of surviving MNs is significantly reduced. This observation has been interpreted by many to suggest the selective resistance of γ-MNs, whereas others explain the finding as a result of cell shrinkage that precedes cell body loss (22)(23)(24)(25)(26)(27)29). To distinguish between these possibilities, we took advantage of our previous studies in which we identified γ-MNs by the absence of NeuN staining and failure to express the Hb9::GFP transgene (17,18 (Fig.…”
Section: γ-Mns Are Selectively Spared At the End Stage Of Disease In mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, aberrant accumulations of NFs are a common pathological hallmark in both sporadic and familial ALS (13)(14)(15) as well as in some mutant SOD1 mouse models (5,16,17). NFs are obligate heteropolymers of NF light (NF-L), NF medium (NF-M), and NF heavy (NF-H) subunits (18,19) and are the most abundant structural components of large myelinated axons, the neurons most at risk in human ALS (20) and mutant SOD1 mouse models (7). The large tail domains of NF-M and NF-H are nearly stochiometrically phosphorylated and are responsible for assembly of a 3D, crosslinked axoplasm that supports acquisition of normal axonal caliber (21).…”
mentioning
confidence: 99%